Electric Waste Collecting Vessel (EWOV) – Citarum River - Lam Khin Xiang; Ahmad Nasirudin (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2019)
This waste collecting vessel is specifically designed to assist with the clean up of the 300km Citarum River, the longest and largest river in Indonesia. This vessel has the capacity of cleaning at least 5.4 tons of waste per day. In a country highly dependent on cheap fossil fuel, Indonesia has yet to ride on the wave of clean energy revolution due to its high initial cost of investment. The vessel uses rechargeable batteries as a source of energy for propulsion and to reduce impact on the environment in contrast to using combustion engine. The method used for this design is The Parrent Vessel Approach. The main dimension of the vessel is determined to be LOA = 8 m, B = 3 m, T = 0.2 m, H = 0.7 m, B1 = 0.7 m, Cb = 0.977, with 3 knots service speed and operating duration of at least 1.3 hours, motor power requirement to be 0.756 kW with 2.685 Wh per battery capacity. The payload capacity is 1.8 tons per round of waste collection. Garbage’s density in general is 481 kg/m^3